Internalization of Moral Development Through the Madrasah Diniyah Program - Astuti, Rini Widia; Syam, Aldo Redho; Sumaryanti, Lilis (Arfannur: Journal of Islamic Education, 2025)
The purpose of this study was to explore the learning of the Madrasah Diniyah Education Program (Madin) at SDN Singosaren 1 Ponorogo towards the internalization of moral values. Madin as a non-formal institution in education that teaches Islamic values, including morals, which are very important for building student character. This study uses a qualitative methodology, which involves data collection through observation, interviews, and documentation. The results of the study indicate that the Madin program helps students understand religious theory and apply morality in everyday life. Students are educated to have a disciplined attitude, respect their elders, and avoid negative behavior with the help of experienced teachers. Parental support is also important for the success of this program, because many parents want the Madin program every day. Therefore, the Madin program is considered an effort to improve the morality of students in schools. This program is implemented after school hours by involving religious teachers and competent educators. The main obstacle found is the influence of technology and gadgets that hinder the internalization of Islamic values optimally. However, this program has succeeded in forming students' religious character through habituation and integration of moral values in daily life. The results of the study showed that the implementation of the Madin program at SDN Singosaren 1 Ponorogo included congregational prayer activities, learning the Quran, and strengthening discipline.